Forecasting of murder crimes using classical and machine learning models - Ayesha Haider; Muhammad Ijaz; Fatimah Essa Almuhayfith; Randa Alharbi; Irum Sajjad Dar (Next Research, 2026)

Carbon nanotube–interfaced lab-on-a-chip sensor coupled with a quantum dot sandwich assay for rapid and selective detection of airborne Aspergillus fumigatus spores - Roomia Memon; Irum Shaheen; Bekir Özyurt; Abdullah Sert; Javed H. Niazi; Anjum Qureshi (Chemical Engineering Journal, 2026)

Vegetable waste into soil acts as slowly released water and fertilizer to improve current vegetable productivity with less chemical fertilization - Adnan Khan; Ling Zhao; Jing Wang; Yun-Li Xiao; Jian-Ming Li; Hua-Guo Zhu; Shi-Sheng Li; Meng-Ying Li; Habimana Evode; Chang Nan; Muhammad Ashraf; Fu-Jian Mei; et al. (Bioresource Technology, 2026)

Introgression of teosinte branched1 gene from wild-progenitor enhances prolificacy in subtropically-adapted maize - Firoz Hossain; Rajkumar Uttamrao Zunjare; Rashmi Chhabra; Irum Gul; Amitkumar D. Kyada; Elizabeth Mathew; Ravindra K. Kasana; Nitish R. Prakash; Vinay Bhatt; Sunil Neelam; Vignesh Muthusamy (Planta, 2026)

Photocatalytic Degradation of Amoxicillin via Carbon Quantum Dots Coupled with Nitrogen-Doped Tungsten (IV) Oxide: Chemical Method for Reclamation of Drug-Contaminated Wastewater - Irum Shah; Farman Ali; Nisar Ali; Maaz Ullah; Mohammad M. Al-Hinaai; Mohammad Albahri; Amir Said (Water, Air, & Soil Pollution, 2026)

Tuning thermochromic performance of 2D perovskites via Br/Cl doping: Enhanced optical modulation and lowered transition temperature toward building energy efficiency - Huanfeng He; Xin Li; Muhammad Fahim; Sai Liu; Irum Firdous; Tsz Chung Ho; Chi Yan Tso (Chemical Engineering Journal, 2026)

Uncovering the genetic architecture of biomass yield and related traits in Southern US oat germplasm using genome-wide association study - Samuel A. Adewale; Md Ali Babar; Naeem Khan; Janam Prabhat Acharya; Jordan McBreen; Irum Raza; Sudip Kunwar; Victor Silva Signorini; Raja Sekhar Nandety; Jason D. Fiedler (Theoretical and Applied Genetics, 2026)

Fabrication and In-Vitro Evaluation of Floating Tablets of Levofloxacin Hemihydrate for the Local Treatment of Helicobacter Pylori Infection - Abdullah Khan; Asif Nawaz; Kamran Ahmad Khan; Ashfaq Ahmad; Muhammad Israr; Haroon Khan; Muhammad Musa Khan; Irum Farooq; Saima Mahmood (Journal of Pharmaceutical Innovation, 2026)

Modeling backward bifurcation cholera diseases with time delays: insights into treatment impact - Samia Bushnaq; Anwar Zeb; Ayesha Bashir; Hijaz Ahmad; Shumaila Irum; Taha Radwan (Modeling Earth Systems and Environment, 2026)

Attitudes towards passwords sharing in cohabiting partners - Irum Saeed Abbasi; Tom Buchanan; Jayson L. Dibble (The Social Science Journal, 2026)

New bovid fossils from the Dhok Pathan, Middle Siwalik subgroup of Pakistan - Kiran Aftab; Bilawal Ghafoor; Muhammad Akbar Khan; Muhammad Adeeb Babar; Mubashar Hussain; Shamaila Irum (PalZ, 2026)

Mechano-electronic integration of accordion-mechanical energy harvester for angle sensing and energy autarky - Weilu Li; Jasim M. Almardi; Xiangkun Bo; Irum Firdous; Xiangyang Zhang; Walid A. Daoud (Chemical Engineering Journal, 2026)

Assessment of the Korang River's water via ecological risk indices and source apportionment procedures for heavy metals contamination, and evaluation of cancer/non-cancer risks - Fazal Manan; Shujaul Mulk Khan; Irum Asif; Nazir Mohammad; Zeeshan Ahmad; Fatima M. Abbas; Mohamed Hashem (Journal of Contaminant Hydrology, 2026)

Retraction notice to “The construction of novel CuO/SnO2@g-C3N4 photocatalyst for efficient degradation of ciprofloxacin, methylene blue and photoinhibition of bacteria through efficient production of reactive oxygen species” [Environ. Res. Volume 231, Part 1, 15 August 2023, 116086] - Irum Batool; Karma Albalawi; Afaq Ullah Khan; Kamran Tahir; Zia Ul Haq Khan; Magdi E.A. Zaki; Ebraheem Abdu Musad Saleh; Eman A. Alabbad; Talal M. Althagafi; Fahad Abdulaziz (Environmental Research, 2025)

Genome-wide characterization and expression analysis of the chitinase gene family in chickpea (Cicer arietinum L.) for fungal stress resistance - Samra Irum; Mustafa Cilkiz; Noorah Al-Kubaisi; Mohamed S. Elshikh; Rashid Iqbal (Molecular Biology Reports, 2025)

Enrichment of phytoglycogen in sweet corn kernels through genomics-assisted selection - Rashmi Chhabra; Rajkumar U. Zunjare; Irum Gul; Subhra J. Mishra; Hriipulou Duo; Vinay Bhatt; Nisrita Gain; Ravindra K. Kasana; Vignesh Muthusamy; Firoz Hossain (Functional & Integrative Genomics, 2025)

Multiplex CRISPR-Cas9 editing of chlorophyll biosynthesis genes in chickpea via protoplast and Agrobacterium-mediated transformation - Samra Irum; Sudip Biswas; Mustafa Cilkiz; Nikolaos Tsakirpaloglou; Michael J. Thomson; Endang M. Septiningsih (Functional & Integrative Genomics, 2025)

Microalgae-Infused Bioalgal Membranes: Pioneering Sustainable Solutions in Environmental Remediation - Irum Bukhari; Fazal Haq; Wajeeha Naeem; Mehwish Kiran; Iffat Ayesha Khan; Sahid Mehmood; Tariq Aziz; Zeeshan Bashir; Abid Khan (Reviews of Environmental Contamination and Toxicology, 2025)

Physicochemical investigation of groundwater within the confinement of Sargodha city and remediation pathways for contaminants - Irum Fatima; Asadullah Dawood; Abdul Muneeb Khan; Sumayya Kanwal; Zainab Bibi; Akbar Hussain (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Metagenomic analysis of two bread wheat (Triticum aestivum. L.) varieties for exploring rhizosphere Microbiome and culture-able beneficial plant growth-promoting rhizobacteria - Irum Naz; Asghari Bano; Muhammed Sajjad Mirza; Tamoor Ul Hassan (Acta Physiologiae Plantarum, 2025)

Lignocellulosic biomass as a renewable resource: Driving second-generation biofuel innovation from agricultural waste - Irum Bukhari; Fazal Haq; Mehwish Kiran; Tariq Aziz; Sahid Mehmood; Muhammad Haroon (Biomass and Bioenergy, 2025)

Vanadium dioxide - Perovskite tandem smart windows achieve full-spectrum modulation via plasmonic Fabry-Pérot engineering - Qiuyi Shi; Bowen Li; Yuwei Du; Sai Liu; Rui Zhang; Cancheng Jiang; Xin Li; Muhammad Fahim; Irum Firdous; Johnny C.Y. Ho; Chi Yan Tso (Chemical Engineering Journal, 2025)

Emerging Contaminants in Water Systems: Detection, Environmental Impacts, and Sustainable Removal Solutions - Irum Bukhari; Fazal Haq; Mehwish Kiran; Rabia Kundi; Ayesha Kiran (Water, Air, & Soil Pollution, 2025)

Examining the roles of marital status and sex on communication with backburners on social media - Michelle Drouin; Irum Abbasi; Jayson L. Dibble; Brandon T. McDaniel (The Social Science Journal, 2025)

Feather keratin-based hybrid adsorbents: Reproducibility and efficacy in metal removal from synthetic wastewater - Irum Zahara; Muhammad Faisal Irfan; Tariq Siddique; Aman Ullah (Journal of Water Process Engineering, 2025)

Antibiotic contamination in wastewater treatment plant effluents: Current research and future perspectives - Parnika Mishra; Gyanendra Tripathi; Vaishnavi Mishra; Talat Ilyas; Irum; Saba Firdaus; Suhail Ahmad; Alvina Farooqui; Neelam Yadav; Sarvesh Rustagi; Sheikh Shreaz; Rajeshwari Negi; et al. (Environmental Nanotechnology, Monitoring & Management, 2025)

Tuning electronic properties of NiCo2S4 nanofibers through phosphorous doping for optimized oxygen reduction and evolution reactions in Li-O2 batteries - Sana Shoukat; Yichuan Dou; Mingzhu Gao; Dongning Wan; Muhammad Shoaib; Sikandar Iqbal; Amina Tariq; Irum Rafique; Amir Said; Songze Li; Imran Haider; Jun Wang (Chemical Engineering Journal, 2025)

Exploring NCS-g-MA.Acid: Synthesis, Characterization, DFT Study, and Its Dual Function in Dye Adsorption and Antibacterial Efficacy - Irum Bukhari; Fazal Haq; Mehwish Kiran; Ghazanfar Ullah; Shah Masood Ahmad; Iffat Ayesha Khan; Sumbal Bibi; Sayed Badshah (Water, Air, & Soil Pollution, 2025)

Intestinal transplantation in Familial Adenomatous Polyposis - Emilio Canovai; Sarah Upponi; Irum Amin (Familial Cancer, 2025)
In patients with Familial Adenomatous Polyposis (FAP), large desmoid tumors can develop all over the body. However, the most frequent presentation is as large intra-abdominal masses, usually located in the mesentery of the small bowel. From there, they tend to grow and invade both the abdominal wall and/or the retroperitoneal structures. This can cause life-threatening complications such as recurrent abdominal sepsis with fistulation and damage to vital organs. In selected patients, the only option may be radical resection and replacement by intestinal transplantation (ITx). We aimed to review all the current literature on ITx for FAP-related desmoids and provide an update from the largest single-center experience (2007–2024). All patients undergoing ITx for FAP-related desmoid were included. Between 2007 and 2024, 166 ITx was performed in 158 patients at Addenbrooke’s Hospital, Cambridge, UK. Of these, 20 (12%) were for desmoid associated with FAP (10 modified multivisceral transplants, 8 isolated ITx and 2 liver-containing grafts). The five-year all-cause patient survival was 92%, median follow-up was 4.3 years. As the patients presented with very advanced disease, many technical challenges were faced such as: extensive ureteric involvement, abdominal wall fistulation, management of previously formed ileo-anal pouches and extra-abdominal recurrences. Graft selection was another evolving issue, as foregut resection- versus sparing techniques require careful preoperative risk stratification due to increased long-term cancer risk in FAP patients. For certain patients with advanced FAP/desmoid disease, ITx can allow for a radical resection with excellent survival and functional outcomes. However, there is a high degree of initial morbidity associated with the operation and patients should be appropriately counselled. Graft selection and degree of native organ resection requires a careful balanced discussion.

Fabrication of multilayer superhydrophobic and biodegradable filters through electrospinning and electrospraying of PHA-SiO2 biopolymer composites - Johnny Sik Chun Lo; Xu Chen; Siru Chen; Walid A. Daoud; Chi Yan Tso; Irum Firdous; Bhaskar Jyoti Deka; Carol Sze Ki Lin (Chemical Engineering Journal, 2025)

Biochemical and molecular characterization of wheat-associated bacteria: implications for plant growth and disease resistance - Ummat-ul-Habib; Asghari Bano; Motsim Billah; Irum Khan; Naeem Khan (Vegetos, 2025)

Degradation of TeCG catalyzed by graphene quantum Dot-reconstituted magnetic hydrotalcite composites - Yan Huang; Guangda Mu; Weiwei Huan; Yuxiang Yang; Hongmin Yuan; Irum Batool; Pingping Yao; Chengyin Wang; Xiangnong Liu; Chaoying Ni (Chemical Engineering Journal, 2025)

Occurrence of Some Heavy Metals in Drinking Water, Vegetables, and Urine in Rawalpindi and Islamabad, Pakistan—Human Health Risk Assessment - Alfred Ndorwu Barnett; Azka Irum; Deedar Nabi; Muhammad Irfan Khawar; Muhammad Arshad (International Journal of Environmental Research, 2025)

Unveiling the chemical profile, anti-proliferative, pro-apoptotic and anti-migratory effect of Indigofera linifolia in liver and breast cancer cells - Irum Naz; Muhammad Rashid Khan; Saima Ali; Riffat Batool (Biocatalysis and Agricultural Biotechnology, 2024)

Expression of mastitis causing fibrinogen binding protein of gram positive bacteria in genetically engineered switchgrass and antibodies production in mice - Saima Shafique; Nyla Jabeen; Samra Irum; Ansar Mehmood; Khawaja Shafique Ahmad (Physiology and Molecular Biology of Plants, 2024)

Spectroscopic and chromatographic studies of chemical constituents of wild A.pindrow royle: facile foliar fuel for the synthesis of nanomaterials - Sadia Iram; Khuram Shahzad Ahmad; Irum Shaheen; Ahmed M. Aljuwayid; Ghulam Abbas Ashraf (Cell Biochemistry and Biophysics, 2024)

Correction to: Plant aqueous extracts to Control Tribolium castaneum (Herbst) Infestation during Rice and Wheat storage - Rehana Naseer; Ifra Imtiaz; Sumia Akram; Zainab Liaqat; Irum Liaqat; Muhammad Mushtaq (International Journal of Tropical Insect Science, 2024)

Retraction Note: Arsenic in drinking water: overview of removal strategies and role of chitosan biosorbent for its remediation - Asif Ayub; Khaysy Srithilat; Irum Fatima; Nadia Masaya Panduro-Tenazoa; Iqbal Ahmed; Muhammad Usman Akhtar; Waqas Shabbir; Khalil Ahmad; Ali Muhammad (Environmental Science and Pollution Research, 2024)

Fabrication of biodegradable PLA-PHBV medical textiles via electrospinning for healthcare apparel and personal protective equipment - Johnny Sik Chun Lo; Xu Chen; Siru Chen; Yahui Miao; Walid A. Daoud; Chi Yan Tso; Irum Firdous; Bhaskar Jyoti Deka; Carol Sze Ki Lin (Sustainable Chemistry and Pharmacy, 2024)

Degradation of trichloroacetic acid by Fe/Ni bimetallic reactive PMS with hierarchical layered structure - Guangda Mu; Yuxiang Yang; Ziling Chang; Hongming Yuan; Yan Huang; Irum Batool; Xiangnong Liu; Chaoying Ni (Environmental Research, 2024)

Do climate change policies, and environmental regulations affect the financial performance: policy-based analysis in context of green innovation - Li Yang; Irum Shahzadi; Xiaowei Feng; Abdelmohsen A. Nassani (Environment, Development and Sustainability, 2024)

Nexus between climate change, agricultural output, fertilizer use, agriculture soil emissions: Novel implications in the context of environmental management - Biao Ma; Mohammad Sharif Karimi; Kamel Si Mohammed; Irum Shahzadi; Jiapeng Dai (Journal of Cleaner Production, 2024)

Spatiotemporal distribution and population trends of Sindh ibex (Capra aegagrus blythii) in Balochistan during 2019–2022 - Najeeb Ullah; Irum Basheer; Zhang Minghai; Muhammad Nawaz Rajpar; Muhammad Rehan; Muhammad Tayyab Khan (European Journal of Wildlife Research, 2024)
The increased pressures generated by human activities in form of climate change and habitat fragmentation have caused serious threats for Sindh ibex ( Capra aegagrus blythii ). Balochistan, recognized as one of the most vulnerable regions to climate change in Pakistan, has limited data on the distribution and population status of this species. To address this gap, our study aims to assess the spatial and temporal distribution and population trend of Sindh ibex in the Khuzdar and Lasbela districts of Balochistan. The study covered an area of approximately 45,123.97 km 2 . It involved a double-observer survey at ten sites from 2019 to 2022, using the BBRecapture package in the R programming language to estimate ibex population trend and dispersion. We provided a comprehensive update of the species geographic range, along with estimates of its current abundance and population trends. Over the course of four years, the ibex population fluctuated. The ibexes detected dropped from 720 (male to female ratio 1:1.21) and 710 (male to female ratio 1:1.08) in 2019 and 2020, respectively, to 550 (male to female ratio 1:1.35) and 548 (male to female ratio 1:1.09). Overall, this study provides valuable insights into the population trends, gender ratios, habitat preferences, and density of Sindh ibex in Balochistan over the four-year period. These findings contribute significantly to the baseline data on the species ecology and will further help in the conservation of these species at local scale.

Plant aqueous extracts to Control Tribolium castaneum (Herbst) Infestation during Rice and Wheat storage - Rehana Naseer; Ifra Imtiaz; Sumia Akram; Zainab Liaqat; Irum Liaqat; Muhammad Mushtaq (International Journal of Tropical Insect Science, 2024)

Using organic fertilizer to mitigate organic-inorganic fouling in agricultural saline wastewater irrigation systems - Tahir Muhammad; Cuiling Jiang; Zeyuan Liu; Irum Manan; Yang Xiao; Yunkai Li (Chemosphere, 2024)

Plant chitinases: Types, structural classification, antifungal potential and transgenic expression in plants for enhanced disease resistance - Raham Sher Khan; Aneela Iqbal; Anam Bibi; Irum Khalil; Zia Ul Islam; Farooq Jan; Asaad Khalid; Ashraf N. Abdalla; Abdul Wadood (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Impacts and mechanism of coal fly ash on kitchen waste composting performance: The perspective of microbial community - Tahir Muhammad; Cuiling Jiang; Yunkai Li; Irum Manan; Changjian Ma; Hui Geng; Iza Fatima; Muhammad Adnan (Chemosphere, 2024)

Higher cadmium and zinc accumulation in parsley (Petroselinum crispum) roots activates its antioxidants defense system - Ismat Nawaz; Atifa Mehboob; Aqib Hassan Ali Khan; Tatheer Alam Naqvi; Nazneen Bangash; Sadia Aziz; Wajiha Khan; Irum Shahzadi; Rocío Barros; Kifayat Ullah; Mohammad Maroof Shah (BioMetals, 2024)

Size and concentration effects of polythene plastic residues on soil physiochemical traits and maize productivity: A three-year appraisal - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Momena Irum; Fei Mo; Jing Cao; Ning Wang; Hong-Yan Tao; Meng Hao; Song Wang; Kai-Wen Xiao; Fang-Kun Yang; et al. (Journal of Cleaner Production, 2024)

Novel cytotoxicity study of strontium (Sr) doped iron oxide (Fe3O4) nanoparticles aided with ibuprofen for drug delivery applications - Imad Ud Din; Irum Shahid Khan; Iftikhar Hussain Gul; Zakir Hussain; Waheed Miran; Farhan Javaid; Usman Liaqat (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Linkages between greenness, socioeconomic conditions, air pollution, and public health in China: does income inequality matters? - Mengyao Hu; Irum Shahzadi; Syed Ali Raza; Xiuhong Niu (Air Quality, Atmosphere & Health, 2024)

Fabrication and Evaluation of Differential Release Bilayer Tablets of Clarithromycin and Levofloxacin by 3D Printing - Qazi Amir Ijaz; Sumera Latif; Sumaira Irum Khan; Memoona Rashid; Hafsa Afzal; Nasrullah Jan; Zeeshan Javaid; Muhammad Sarfraz; Amjad Hussain; Muhammad Sohail Arshad; Nadeem Irfan Bukhari; Nasir Abbas (Journal of Pharmaceutical Innovation, 2023)

LC-ESI-MS analysis, antioxidant, anti-diabetic and molecular docking studies on Corchorus depressus (L.) C.Chr - Shazia Anjum; Humna Tahir; Sadia Sarwar; Wajid Raza; Irum Latif; Hafiz Muhammad Farhan Rasheed; Qaiser Jabeen; Wardah Shahid; Muhammad Ashraf; Syeda Sadaf Zehra; Zaheer Ul-Haq; Muhammad Ayaz; et al. (Natural Product Research, 2023)

Synthesis & fabrication of O-linked polymeric hybrids for recovery of textile dyes: Closed loop economy - Irum Asif; Uzaira Rafique (Environmental Research, 2023)

Elucidating growth and biochemical characteristics of rice seedlings under stress from chromium VI salt and nanoparticles - Maryam Noor; Arif Ullah; Muhammad Israr Khan; Irum Raza; Muhammad Iqbal; Abdul Aziz; Gil Won Kim; Nadia Taimur; Azizullah Azizullah; Imran Ali; Pil Joo Kim (Environmental Science and Pollution Research, 2023)

First report of Rhizopus microsporus causing soft rot in apple fruit in Pakistan - Shameel Pervez; Saad Durrani; Rumaisa Shahid; Irum Mukhtar; Ibatsam Khokhar (Journal of Plant Pathology, 2023)

Preparation and characterization of single perovskite microplates and its sunlight assisted photodecolorization activity, validated by response surface methodology - Arif Nawaz; Irum Naz; Muhammad Atif; Adnan Khan; Nisar Ali (Chemosphere, 2023)

Removal of divalent cations and oxyanions by keratin-derived sorbents: Influence of process parameters and mechanistic studies - Irum Zahara; Muhammad Faisal Irfan; Muhammad Zubair; Tariq Siddique; Aman Ullah (Science of The Total Environment, 2023)

Quercetin supplementation in the diet of Labeo rohita: Effects on growth, proximate composition, antioxidative indices and immunity - Tahrim Khan; Mahroze Fatima; Syed Zakir Hussain Shah; Noor Khan; Maryam; Wazir Ali; Atiqa Sabir; Irum Tahir; Dua Laraib (Animal Feed Science and Technology, 2023)

Assessment of cytotoxic potential of newly isolated Betulinic triterpenes from the Bark of Bauhinia variegata Linn. (Caesalpiniaceae) - Yousaf Kamal; Taous Khan; Nighat Fatima; Irum Shahzadi; Ihsan ul-Haq; Gerardo D. Anaya-Eugenio; Eric Daniel Salinas Arellano; Kashif Bashir; Esperanza J Carcache de Blanco (South African Journal of Botany, 2023)

Identification and comparative analysis of Histidine phosphotransfer (HP) genes reveal their role in cotton development and stress tolerance - Nosheen Kabir; Sumbal Wahid; Sehrish Sarfraz; Zulqurnain Khan; Ummara Waheed; Maria Siddique; Irum Shahzadi; Umar Akram; Shoaib Ur Rehman; Ghulam Qanmber (South African Journal of Botany, 2023)

RETRACTED: The construction of novel CuO/SnO2@g-C3N4 photocatalyst for efficient degradation of ciprofloxacin, methylene blue and photoinhibition of bacteria through efficient production of reactive oxygen species - Irum Batool; Karma Albalawi; Afaq Ullah Khan; Kamran Tahir; Zia Ul Haq Khan; Magdi E.A. Zaki; Ebraheem Abdu Musad Saleh; Eman A. Alabbad; Talal M. Althagafi; Fahad Abdulaziz (Environmental Research, 2023)

What do we learn from Nexus between trade diversification and structural change: informing the future about climate action and Sustainability - Buhari Doğan; Amar Rao; Diogo Ferraz; Gagan Deep Sharma; Irum Shahzadi (Environmental Science and Pollution Research, 2023)

Natural resources and environmental sustainability: COP26 targets from resources-based perspective - Li Peng; Yongchang Li; Syed Ali Raza; Irum Shahzadi (Resources Policy, 2023)

Mine Wastewater Treatment with Upflow Anaerobic Fixed Film Reactors - Islamud Din; Sardar Khan; Abd El-Latif Hesham; Sidra Irum; Cang Daqiang (Mine Water and the Environment, 2023)

Electrophoretic Fabrication of ZnO/CuO and ZnO/CuO/rGO Heterostructures-based Thin Films as Environmental Benign Flexible Electrode for Supercapacitor - Irum Shaheen; Iftikhar Hussain; Taghazal Zahra; Roomia Memon; Asma A. Alothman; Mohamed Ouladsmane; Anjum Qureshi; Javed H. Niazi (Chemosphere, 2023)

Accumulation of heavy metals in wild plants collected from the industrial sites—potential for phytoremediation - I. Ahmad; I. Gul; S. Irum; M. Manzoor; M. Arshad (International Journal of Environmental Science and Technology, 2023)

Binder-free cupric-ion containing zinc sulfide nanoplates-like structure for flexible energy storage devices - Iftikhar Hussain; Irum Shaheen; Rabia Ahmad; Ijaz Ali; Khurshid Hussain; Sayed Sajid Hussain; Norah Salem Alsaiari; Khadijah Mohammedsaleh Katubi; Sayed M. Eldin; Mohd Zahid Ansari (Chemosphere, 2023)

High power-output and highly stretchable protein-based biomechanical energy harvester - Xiangkun Bo; Kindness A. Uyanga; Lingyun Wang; Irum Firdous; Jihong Shi; Weilu Li; Jasim M. Almardi; Muhammad Fahim; Fei Liu; Huanlin Lyu; Walid A. Daoud (Chemical Engineering Journal, 2023)

Does geothermal energy and natural resources affect environmental sustainability? Evidence in the lens of sustainable development - Muhammad Adnan Bashir; Zhao Dengfeng; Irum Shahzadi; Muhammad Farhan Bashir (Environmental Science and Pollution Research, 2022)

Assessing the EKC hypothesis by considering the supply chain disruption and greener energy: findings in the lens of sustainable development goals - Kamel Si Mohammed; Sunil Tiwari; Diogo Ferraz; Irum Shahzadi (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Arsenic in drinking water: overview of removal strategies and role of chitosan biosorbent for its remediation - Asif Ayub; Khaysy Srithilat; Irum Fatima; Nadia Masaya Panduro-Tenazoa; Iqbal Ahmed; Muhammad Usman Akhtar; Waqas Shabbir; Khalil Ahmad; Ali Muhammad (Environmental Science and Pollution Research, 2022)

A sustainable generalization of inverse Lindley distribution for wind speed analysis in certain regions of Pakistan - Muhammad Shoaib; Irum Sajjad Dar; Muhammad Ahsan-ul-Haq; Rana Muhammad Usman (Modeling Earth Systems and Environment, 2022)

In-Silico Vaccine Design Based on a Novel Vaccine Candidate Against Infections Caused by Acinetobacter baumannii - Kashaf Khalid; Sidra Irum; Sidra Rahmat Ullah; Saadia Andleeb (International Journal of Peptide Research and Therapeutics, 2022)

Quest for Novel Preventive and Therapeutic Options Against Multidrug-Resistant Pseudomonas aeruginosa - Sidra Irum; Saadia Andleeb; Amjad Ali; Muhammad Ibrahim Rashid; Mahnoor Majid (International Journal of Peptide Research and Therapeutics, 2021)

The Fvclp1 gene regulates mycelial growth and fruiting body development in edible mushroom Flammulina velutipes - Xiaomeng Lyu; Siyuan Jiang; Li Wang; Tiansheng Chou; Qingji Wang; Li Meng; Irum Mukhtar; Baogui Xie; Wei Wang (Archives of Microbiology, 2021)

LC–MS/MS-based profiling of bioactive metabolites of endophytic bacteria from Cannabis sativa and their anti-Phytophthora activity - Irum Iqrar; Muhammad Numan; Tariq Khan; Zabta Khan Shinwari; Gul Shad Ali (Antonie van Leeuwenhoek, 2021)

Impact of race on outcomes in intermediate-risk acute myeloid leukemia - Ivy Elizabeth Abraham; Anand Ashwin Patel; Heidy Wang; John Patrick Galvin; Olga Frankfurt; Li Liu; Irum Khan (Cancer Causes & Control, 2021)

Exploration of microbiome of medicinally important plants as biocontrol agents against Phytophthora parasitica - Irum Iqrar; Zabta Khan Shinwari; Ashraf Sabry Abdel Fatah El-Sayed; Gul Shad Ali (Archives of Microbiology, 2021)

Genome-Wide Characterization of the Nuclear Receptor Gene Family in Macrostomum lignano Imply Its Evolutionary Diversification - Yunying Cheng; Jinlin Chen; Irum Mukhtar; Jianming Chen (Frontiers in Marine Science, 2021)
Nuclear receptors ( NRs ), a series of key transcription factors that are mostly activated by endogenous ligands or environmental xenobiotics, are reportedly good phylogenetic markers of animal genome evolution. As the early diverging class of bilaterians, however, a comprehensive view of the NR family in a marine free-living flatworm Macrostomum lignano and comparative information in flatworms are still lacking, which is of significance to address the evolutionary diversification of the NR family and imply the adaptive evolution in the early diverging Bilateria. Herein, a total of 51, 26, and 23 putative NR genes were identified in M. lignano , Sparganum proliferum , and Clonorchis sinensis , respectively, which were classified into eight subfamilies, implying an extensive expansion of the NR family in M. lignano . It is presumed that the extensive expansion was mainly attributed to the M. lignano -specific hidden polyploidy, segmental, and tandem duplication events. The duplicated NR pairs in M. lignano and the NR orthologs in flatworms all experienced the purifying selection. Phylogenetic analyses indicated the presence of NR3 -like genes in M. lignano , which is first reported in flatworms. Intron loss and reduced intron size were mainly contributed to the structural divergence of NR genes in flatworms. The combined data provide indispensable information for a better understanding of the complexity and the adaptive evolution of the NR gene family in metazoans.

A missense allele of PEX5 is responsible for the defective import of PTS2 cargo proteins into peroxisomes - Muhammad Ali; Shahid Y. Khan; Tony A. Rodrigues; Tânia Francisco; Xiaodong Jiao; Hang Qi; Firoz Kabir; Bushra Irum; Bushra Rauf; Asma A. Khan; Azra Mehmood; Muhammad Asif Naeem; et al. (Human Genetics, 2021)

Characterization and expression pattern analysis of pheromone receptor-like genes in Winter Mushroom Flammulina filiformis - Li Meng; Tiansheng Chou; Siyuan Jiang; Li Wang; Mengjuan Zhu; Irum Mukhtar; Baogui Xie; Wei Wang (Archives of Microbiology, 2020)

Synthesis, characterization, and biocompatibility of lanthanum titanate nanoparticles in albino mice in a sex-specific manner - Irum Naz Akram; Sana Akhtar; Ghulam Khadija; Mian Muhammad Awais; Muhammad Latif; Aasia Noreen; Mehwish Mobeen; Fareeha Sajjad; Zahida Sardar; Shahid Iqbal; Muhammad Naeem Ashiq; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Datura suaveolens and Verbena tenuisecta mediated silver nanoparticles, their photodynamic cytotoxic and antimicrobial evaluation - Ahsan Ashraf; Nighat Fatima; Irum Shahzadi; Hina Tariq; Anam Shahzadi; Muhammad Arfat Yameen; Jamshed Iqbal; Muhammad Rafi (World Journal of Microbiology and Biotechnology, 2020)

Inhibition of Hyperuricemia and Gouty Arthritis in BALB/c Mice Using Copper Oxide Nanoparticles - Mubin Mustafa Kiyani; Hamza Rehman; Mir Arif Hussain; Saira Jahan; Muhammad Afzal; Irum Nawaz; Tariq Mahmood; Syed Ali Imran Bokhari (Biological Trace Element Research, 2020)

First report of Gilbertella persicaria causing soft rot in eggplant fruit in China - Ibatsam Khokhar; Irum Mukhtar; Junhuan Wang; Yang Jia; YanChun Yan (Journal of Plant Pathology, 2019)

Oral supplementation of Lanthanum Zirconate nanoparticles moderately affected behavior but drastically disturbed leukocyte count, serum cholesterol levels and antioxidant parameters from vital organs of albino mice in a gender specific manner - Muhammad Nazar Aftab; Irum Naz Akram; Tafheem Khosa; Syeda Qandeel Zahra; Irum Bashir; Muhammad Naeem Ashiq; Furhan Iqbal (Metabolic Brain Disease, 2018)

Resistance in field populations of Amrasca devastans (Hemiptera: Cicadellidae) to new insecticides in Southern Punjab, Pakistan - Nasir Abbas; Naeem Abbas; Masood Ejaz; Sarfraz Ali Shad; Iqra Asghar; Aima Irum; Muhammad Binyameen (Phytoparasitica, 2018)

Molecular identification and control of endophytic contamination during in vitro plantlet development of Fagonia indica - Tariq Khan; Bilal Haider Abbasi; Irum Iqrar; Mubarak Ali Khan; Zabta Khan Shinwari (Acta Physiologiae Plantarum, 2018)

Assessment of field evolved resistance to some broad-spectrum insecticides in cotton jassid, Amrasca devastans from southern Punjab, Pakistan - Nasir Abbas; Muhammad Ismail; Masood Ejaz; Iqra Asghar; Aima Irum; Sarfraz Ali Shad; Muhammad Binyameen (Phytoparasitica, 2018)

Ag-loaded thermo-sensitive composite microgels for enhanced catalytic reduction of methylene blue - Luqman Ali Shah; Murtaza Sayed; Muhammad Fayaz; Irum Bibi; Mohsan Nawaz; Mohammad Siddiq (Nanotechnology for Environmental Engineering, 2017)

Chaetomium endophytes: a repository of pharmacologically active metabolites - Nighat Fatima; Syed Aun Muhammad; Ibrar Khan; Muneer Ahmed Qazi; Irum Shahzadi; Amara Mumtaz; Muhammad Ali Hashmi; Abida Kalsoom Khan; Tariq Ismail (Acta Physiologiae Plantarum, 2016)

Arabidopsis thaliana MCM3 single subunit of MCM2–7 complex functions as 3′ to 5′ DNA helicase - Irum Rizvi; Nirupam Roy Choudhury; Narendra Tuteja (Protoplasma, 2016)

Insights into the functional characteristics of geminivirus rolling-circle replication initiator protein and its interaction with host factors affecting viral DNA replication - Irum Rizvi; Nirupam Roy Choudhury; Narendra Tuteja (Archives of Virology, 2015)

Novel malyngamide structural analogs: synthesis and biological evaluation - G. Venkateswar Reddy; T. Vijaya Kumar; B. Siva; K. Suresh Babu; P. V. Srinivas; Irum Sehar; A. K. Saxena; J. Madhusudana Rao (Medicinal Chemistry Research, 2013)

Constrains on mangrove forests and conservation projects in Pakistan - Irum Mukhtar; Abdul Hannan (Journal of Coastal Conservation, 2012)

Biochemical, molecular characterization and growth promoting effects of phosphate solubilizing Pseudomonas sp. isolated from weeds grown in salt range of Pakistan - Irum Naz; Asghari Bano (Plant and Soil, 2010)

Cultures of human tracheal gland cells of mucous or serous phenotype - Walter E. Finkbeiner; Lorna T. Zlock; Irum Mehdi; Jonathan H. Widdicombe (In Vitro Cellular & Developmental Biology - Animal, 2010)

Mobilisation into cotton and spread of a recombinant cotton leaf curl disease satellite - I. Amin; S. Mansoor; L. Amrao; M. Hussain; S. Irum; Y. Zafar; S. E. Bull; R. W. Briddon (Archives of Virology, 2006)